The relationship of cutting chip type, length and thickness to wear of Zirconia Toughened Alumina Added with Magnesium Oxide (ZTA-MgO) cutting tool - Mohd Ali, Afifah; Janal, Nurul Nabihah; Hamidon, Nor Ezzati; Ahmad Azhar, Ahmad Zahirani; Mokhtar, Suhaily; Bahar, Rubina; Ahmad, Zainal Arifin (UR Publishers, 2018)
The effect of cutting chips on the performances of ZTA-MgO ceramic cutting tool investigated. The aim of this project is to discover the effect of cutting chip type, length and thickness on the wear of the ZTA-MgO cutting tool. CNC turning machining performed by using Rom-Bridgeport CNC turning machine at cutting speed range from 2250 to 3000 rpm, the feed rate 0.1, 0.3 and 0.5 mm/rev while the depth of cut is kept constant at 0.2 mm. The flank wear and crater wear were measured accordingly using optical microscope, Matlab programming and SEM. The chip type, length and thickness were classified and measured. The variation of cutting parameters influenced the chip geometry and it relation to tool wear were analysed. The chips were collected. The chip type, length and thickness analysed using optical microscope and SEM. Result shows chip started with tubular and ribbon form of chip. Increment of feed rate, make the chip break to smaller part. The chip length increase when cutting speed was increased. The chip is 2.49 cm length at cutting speed 2250 rpm increased up to 4.61 cm at 3000 rpm. The chip thickness was increased with increasing of feed rate where the average thickness is at lowest when the feedrate is at 0.1mm/rev and highest at 0.5 mm/rev all cutting speed. The increment of chip length caused the crater wear increased on cutting tool from 5.66 mm2 at chip length of 2.49 cm and increased to 7.40 mm2 when the length increased to 4.61 cm. The high chip thickness caused higher flank wear on the cutting tool. Based on the analysis, the chip type, length and thickness have influence on flank and crater wear of the ZTA-MgO cutting tool which may lead to failure of the cutting tool.